Determining the resistance or susceptibility of grapevine rootstocks used in South Africa towards fungal trunk disease pathogens - Sieberhagen, Madeleine (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.